Development of a Self‐Deploying Extra‐Aortic Compression Device for Medium‐Term Hemodynamic Stabilization: A Feasibility Study - Adrienne Ji; James Davies; Phuoc Thien Phan; Chi Cong Nguyen; Bibhu Sharma; Kefan Zhu; Emanuele Nicotra; Jingjing Wan; Hoang‐Phuong Phan; Christopher Hayward; Nigel H. Lovell; Thanh Nho Do (Advanced Science)
Abstract Hemodynamic stabilization is crucial in managing acute cardiac events, where compromised blood flow can lead to severe complications and increased mortality. Conditions like decompensated heart failure (HF) and cardiogenic shock require rapid and effective hemodynamic support. Current mechanical assistive devices, such as intra‐aortic balloon pumps (IABP) and extracorporeal membrane oxygenation (ECMO), offer temporary stabilization but are limited to short‐term use due to risks associated with prolonged blood contact. This research presents a novel proof‐of‐concept soft robotic device designed with the aim of achieving low‐risk, medium‐term counterpulsation therapy. The device employs a nature‐inspired growing mechanism for potentially minimally invasive deployment around the ascending aorta, coupled with hydraulic artificial muscles for aortic compression. It demonstrated a maximum stroke volume of 16.48 ± 0.21 mL (SD, n = 5), outperforming all other non‐pneumatic extra‐aortic devices. In addition, in vitro tests with a mock circulation loop (MCL) show a drop in aortic end‐diastolic pressure by 6.32 mmHg and enhance coronary flow under mild aortic stenosis, which attenuate the device's assistive effect. These findings highlight the device's strong potential for optimization as a promising solution to improve outcomes for hemodynamically unstable HF patients.